Analisis Potensi Usahatani Nenas Dalam Upaya Meningkatkan Pendapatan Dan Kesejahteraan Desa Mekarsari Kabupaten Barito Kuala - Risma; Sopiana , Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The research was conducted in order to aim at analyzing the level of income in the welfare of the farming community of Mekarsari Village, Barito Kuala Regency. The choice of place of research is based on information from the Mekarsari Village Chief that Mekarsari Village is the village that produces the most pineaplle. The number of respondens in the study 41 respondents. The analytical method used is desriptive qualitative analysis, quantitative analysis. The results showed that: (1) the average income of pineapple farmers in the village of Mekarsari was Rp. 78.935.366 this income according to BPS was in the medium category of Rp. 50.000.000 – Rp. 100.000.000. (2) The level of welfare of pineapple farmers in the village of Mekarsari enter into prosperous farmers because the average farmers there hastheir own land, so farmers there can enjoy their own results.